1995
DOI: 10.1017/s0813483900004356
|View full text |Cite
|
Sign up to set email alerts
|

An Intervention for Substance Abuse in Schizophrenia

Abstract: Substance abuse in schizophrenia is a significant management problem for both clients and treatment agencies, impacting on psychotic symptoms, medication adherence, and participation in training and employment. However, there is little published work on the treatment of drug abuse in this population. This paper describes a cognitive-behavioural intervention for alcohol and cannabis abuse which integrates substance abuse treatment with other aspects of psychosis management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
0
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 67 publications
2
39
0
1
Order By: Relevance
“…There is now substantial evidence that substance abuse in people with psychiatric disorders leads to poorer functional and symptomatic outcomes, and to higher treatment costs [6][7][8]. Substance use in psychosis can lead to housing instability, poorer self-care, concurrent medical disorders, antisocial relationships and disrupted motivation [6]. Substance use in psychosis can lead to housing instability, poorer self-care, concurrent medical disorders, antisocial relationships and disrupted motivation [6].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…There is now substantial evidence that substance abuse in people with psychiatric disorders leads to poorer functional and symptomatic outcomes, and to higher treatment costs [6][7][8]. Substance use in psychosis can lead to housing instability, poorer self-care, concurrent medical disorders, antisocial relationships and disrupted motivation [6]. Substance use in psychosis can lead to housing instability, poorer self-care, concurrent medical disorders, antisocial relationships and disrupted motivation [6].…”
mentioning
confidence: 99%
“…Substance abuse may lead to anxiety and depression and these are also exacerbated by intoxication by or withdrawal from several substances [11][12][13] and in some cases, substantial recovery can be obtained after a period of abstinence from substance use [12]. Despite the importance of the issue, the treatment of comorbid substance misuse and mental health problems has attracted very little research [6,7,17]. The association between substance misuse and mental health disorders is therefore an important and complex one.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dif fé rents pro gram mes de trai te ments in té grés ont été dé ve lop pés au cours des der niè res an nées afin de ré pon dre aux be soins des per sonnes pré sen tant une co mor bi dité (Brady et al, 1996;Carey, 1996;Drake et al, 1991;Kavanagh, 1995;Minkoff, 1989;Osher et Kofoed, 1989;Rosenthal et al, 1992;Ziedonis et Fisher, 1996). Plu sieurs de ces program mes par ta gent une même phi lo so phie et leur in ter ven tion comprend les mê mes com po san tes fon da men ta les.…”
Section: Les Trai Te Ments In Té Grés De Santé Men Tale Et De Toxi Counclassified
“…Young men living in poor, urban areas have been identified as being at particularly high risk of having these dual problems (Mueser et al, 1992). Several studies have reported particularly high rates of psychosocial difficulties among this group which have in-cluded family discord, financial difficulties, housing instability, homelessness, poor selfcare and legal entanglements (Drake & Wallach, 1989;O'Leary, 1997;Kavanagh, 1995). Several studies have reported particularly high rates of psychosocial difficulties among this group which have in-cluded family discord, financial difficulties, housing instability, homelessness, poor selfcare and legal entanglements (Drake & Wallach, 1989;O'Leary, 1997;Kavanagh, 1995).…”
Section: Introductionmentioning
confidence: 99%